WOOD COLORIMETRY OF NATIVE SPECIES OF MYRTACEAE FROM A ARAUCARIA FOREST - Vieira, Helena Cristina; Lopes da Silva, Eliane; Xipaia dos Santos, Joielan; Inés Bolzon de Muñiz, Graciela; Ribeiro Morrone, Simone; Nisgoski, Silvana (Floresta, 2019)
Colorimetric parameters have potential to differentiate tree species through their wood type. Therefore, this can be used to aid the inspection of illegal trade. Thus, considering the need to identify species with precision and speed, this study aimed to explore the potential of these parameters in order to characterize wood of some species of native Myrtaceae from the Araucaria Forest: Campomanesia xanthocarpa Berg., Eugenia pyriformis Cambess., Myrcia retorta Cambess., and Plinia Peruviana (Poir.) Govaert. Twelve trees were collected randomly – three per species – for the removal of a disc at diameter at breast height (DBH). We took samples from three regions of the disc (next to the bark, intermediate and next to the pith) and analyzed them in three anatomical sections (transversal, radial and tangential) by the system CIE L*a*b* using a bench colorimeter. We analyzed the data based on the following criteria: test of means in order to differentiate species, quantitative factor analysis (considering the region of the disc and the anatomical section as factors), and principal components analysis (PCA). Then, we used the original spectrum and the values of parameters L*, a* and b* in order to verify the distribution of the species. The analysis determined that the species present different values for the colorimetric parameters. In addition, the factors region of the disc and anatomical section have specific influence for each species. Finally, the PCA indicated that only E. pyriformis differs from the others.